Farm eco-efficiency: Can sustainable intensification make the difference? - Meike Weltin; Silke Hüttel (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2019)
Sustainable intensification measures promise ecological improvements of farming while maintaining profitability. That is, farms should be able to produce at a higher ecological efficiency without losses in economic efficiency. Based on a theoretical framework, we investigate this promise empirically by analysing the environmental improvement potential of sustainable intensification. We thereby focus on quantifying biodiversity gains using a directional meta-frontier approach and farm survey data from the northern German Plain. We compare eco-efficiency scores in an ecological direction between adopters and matched non-adopters to identify the causal relationship between these gains and sustainable intensification. We find that adopters determine the system frontier. Despite higher mean eco-efficiency scores, most adopters do not yet fully exploit the potential of ecological improvements through sustainable intensification.
Keywords: Q12; Q15; Q57; 330; environmental sustainability; eco-efficiency; directional data envelopment analysis; matching